System optimisation and performance analysis of CO2 transcritical power cycle for waste heat recovery. (1st April 2016) - Wu, Chuang; Yan, Xiao-jiang; Wang, Shun-sen; Bai, Kun-lun; Di, Juan; Cheng, Shang-fang; Li, Jun
Abstract: Compared with the ORC (organic Rankine cycle) and the steam Rankine cycle, the CDTPC (CO2 (carbon dioxide) transcritical power cycle) shows a higher potential in converting middle-grade waste heat into useful work. In this paper, we propose a novel type of single-pressure, multi-stage CDTPC to overcome the shortcomings of the CDTPC in utilizing waste heat of exhaust gas from gas turbines or internal combustion engines. System parameter optimization is carried out in various CDTPC to achieve the maximum net power output of cycle by using the genetic algorithm(GA). A comparative study between the existing CDTPC and the proposed novel type of CDTPC with the same exhaust gas temperature T gi (250–500 °C) at the inlet of the gas heater shows that the novel type of CDTPC can increase the net power output by 3.9–26.3% and decrease the optimum working pressure by 13.2–31.0%. If exhaust gas is non-corrosive, waste heat can be utilized more effectively by the double-stage CDTPC when 250 °C ≤ T gi ≤ 412 °C and by the three-stage CDTPC when 412 °C < T gi ≤ 500 °C. However, if the exhaust gas is corrosive, waste heat is utilized more effectively by the single-stage CDTPC when 250 °C ≤ T gi ≤ 338 °C and by the double-stage CDTPC when 338 °C < T gi ≤ 500 °C. In addition, the effect of the regenerator on the thermal performance of various CDTPC is studied. Highlights: We put forward a new type of single-pressure, multi-stage CDTPC for waste heat recovery. System parameter optimization was carried out by using the genetic algorithm. The optimum pressure and power output of new cycle were much lower and higher than those of the existing cycle respectively.